Microstructural characteristics and strengthening mechanisms in a polycrystalline Ni-based superalloy under deep cold rolling - Kumar, Dharmesh (2020)
Surface modification is an essential process route to improve the fatigue performance of aerospace components. Microstructural evolution in Ni-based superalloy Udimet720Li processed by deep cold rolling (DCR) was investigated experimentally using X-Ray diffraction, electron back-scattered diffraction (EBSD) and transmission electron microscopy (TEM). Deep cold rolling produces hardened surface due to a range of microstructural changes associated with grain refinement, low angle grain boundaries (LAGBs) formation, and pile-up of dislocations around precipitates and across twin boundaries. The defect structures within the deformed subsurface comprised of equiaxed and elongated dislocation cells at grain boundaries, mutual interactions of slip bands, slip bands- precipitate at grain boundaries and multi-variant modes of twinning. The plastic deformation is predominantly driven through slip and dislocation multiplication mechanism during DCR. Surface compressive residual stresses, FWHM, micro-hardness, the fraction of LAGBs and the depth of plastically strained region increased with DCR hydrostatic pressure. These fundamental understanding on process-microstructure-property could provide a deep insight into the fatigue crack initiation mechanism of surface modified Ni-based superalloys.